Integrated Community Health Promotion through Education, Screening, and Preventive Interventions in Rejomulyo Village, Kediri - Reni Nurhidayah; Yuly Peristiowati; Sutrisno; Atik Setiawan; Joko Sutrisno; Agusta Dian Elina; Muhamad As’ad Efendi; Kurniawan Edi Priyanto; Dedi Saifulah; Fajar Rinawati (Journal of Community Engagement in Health, 2026)
Community health problems in Indonesia are increasingly complex, including the rising burden of non-communicable diseases, communicable diseases, nutritional issues, and psychosocial problems, particularly among vulnerable populations such as the elderly. This community service aimed to implement an integrated community health promotion program through education, screening, and preventive interventions in Rejomulyo Village, Kediri. This study used a community-based participatory approach with a descriptive evaluative design. The program involved approximately 65 participants and included health education sessions, health screenings (vital signs, anthropometry, biochemical tests, and physical function assessment), and preventive interventions such as local food-based supplementary feeding and smoke-free household promotion. Data were collected through observation, screening records, and participant responses, and analyzed descriptively.The results showed that a significant proportion of participants were at risk of non-communicable diseases, including hypertension, elevated blood glucose, and abnormal nutritional status. Health education activities improved participants’ knowledge and awareness of disease prevention, clean and healthy living behaviors, and environmental health risks. Preventive interventions were well accepted, with increased community commitment to adopting healthier lifestyles, including routine health monitoring and smoke-free home practices.In conclusion, the integrated approach combining education, screening, and preventive interventions proved effective in improving community awareness, enabling early detection of health risks, and promoting sustainable health behaviors. This model has the potential to be replicated in other communities to enhance public health outcomes.